2013
DOI: 10.2147/ijgm.s42853
|View full text |Cite
|
Sign up to set email alerts
|

West Nile virus infection and diplopia: a case report and review of literature

Abstract: West Nile virus is a neurotropic virus transmitted to humans via an infected mosquito bite. The increase in the incidences and fatalities of West Nile virus disease has made West Nile virus an important pathogen. Here we describe a case of a 65-year-old man with fever and diplopia presenting to the emergency department during a fall season and who was later diagnosed with West Nile virus infection. Diplopia is an uncommon manifestation of West Nile virus and recognition of the different modes of presentation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Multifocal chorioretinitis is the most frequent ocular manifestation of WNV infection. However, several ophthalmologic findings have been reported, including iridocyclitis, retinal vasculitis, macular edema, choroidal neovascularization, optic neuropathy, neuroretinitis, congenital chorioretinal scarring, ocular nerve palsy, and nystagmus secondary to encephalitis [ 5 , 11 , 12 ]. Excluding the most severe cases, West Nile chorioretinitis is considered to be a self-limiting pathology if retinal and choroidal complications do not occur, and patients can be watched without treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Multifocal chorioretinitis is the most frequent ocular manifestation of WNV infection. However, several ophthalmologic findings have been reported, including iridocyclitis, retinal vasculitis, macular edema, choroidal neovascularization, optic neuropathy, neuroretinitis, congenital chorioretinal scarring, ocular nerve palsy, and nystagmus secondary to encephalitis [ 5 , 11 , 12 ]. Excluding the most severe cases, West Nile chorioretinitis is considered to be a self-limiting pathology if retinal and choroidal complications do not occur, and patients can be watched without treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[70]. WNV-associated chorioretinitis often presents with minimal symptoms, such as floaters, a mild vision reduction, redness, ocular pain, visual field defects, or diplopia [4,7,67,71,72].…”
Section: Ocular Manifestationsmentioning
confidence: 99%
“…Other manifestations have been described, including non-granulomatous anterior uveitis, retinal hemorrhages, focal or diffuse retinal vascular sheathing, vascular leakage, occlusive vasculitis, congenital chorioretinal scarring, zones of atrophy and mottling of the RPE, macular edema, optic neuritis, papilledema, and binocular diplopia related to sixth cranial nerve involvement [6,7,44,67,68,72,76,77]. Patients (n = 51 eyes) with intraocular inflammation tested positive for WNV-related vitritis (73%), papilledema (14%), intraretinal hemorrhages (43%), vasculitis (32%), and retinal occlusive vasculitis (16%) [71].…”
Section: Ocular Manifestationsmentioning
confidence: 99%
“…Other inflammatory lesions, such as retinitis, macular edema, atrophic lesions of the retinal pigment epithelium, optic disc swelling, optic neuritis, neuroretinitis, and papilledema, have also been reported [ 14 , 17 , 18 , 19 , 20 , 28 ]. Other neuro-ophthalmic manifestations have been described, including retrogeniculate damage, ocular nerve palsy caused by cranial nerve involvement [ 14 , 29 , 30 ], and nystagmus secondary to encephalitis [ 31 , 32 ]. Alpert et al have reported ocular manifestations in the context of congenital infection, where the infant’s mother had developed paraplegia due to WNVI during the second trimester of her pregnancy [ 16 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%